(untitled) (Scientific journal of the Fergana State University, 2024)
In modern vehicles, mainly internal combustion engines are common. In terms of construction, internal combustion engines are divided into porches and rotors. Autom obils mainly use porcelain internal combustion engines. In piston engines, the pressure generated by the combustion of the fuel in the expansion of the gas is absorbed by the piston, and in the direction of straight-line advance and return, the elbow Valve is moved in a circular motion.